Zinc as Adjunct Therapy in Neonatal Sepsis (Medicine Today, 2020)
Introduction:Altered zinc homeostasis is an important feature of pediatric sepsis, thus raising the possibility of zinc supplementation as a therapeutic strategy in neonatal sepsis, a major source of morbidity and mortality with few therapeutic options beyond antibiotics. Its objective was to find the role of zinc as adjunct therapy in neonatal sepsis.Materials and Methods: This prospective, randomized double blind placebo controlled trial was conducted in the Department of Paediatrics, Sylhet M A G Osmani Medical College, Sylhet, Bangladesh during January 2013 to December 2014. A total 288 neonates with neonatal sepsis were enrolled. Group allocation to either zinc or placebo group was done by lottery method. Each packet contained 5 mg dispersible zinc sulphate or placebo. One packet dissolved in 2.5 ml expressed breast milk was given orally or through feeding tube.Results: The age of the patients in zinc group and placebo group was 14.40 ± 6.49 days and 15.09 ± 7.18 days respectively. There were 49 (75.6%) male neonates and 16 (24.6%) female neonates in zinc group; while 50 (78.1%) neonates were male and 14 (21.9%) were female in placebo group. Clinical recovery was 61 (93.8%) and failure in 4 (6.2%) patients in zinc group; while clinical recovery was 59 (92.2%) and failure in 5 (7.8%) patients in placebo group. The mean clinical recovery time in zinc group was 104.20 ± 16.61 hours and that of control groups was 111.46 ± 19.43 hours.Conclusion: Oral zinc as adjunct therapy shortens the clinical recovery time.Medicine Today 2020 Vol.32(2): 112-116